2010
DOI: 10.1242/jeb.048686
|View full text |Cite
|
Sign up to set email alerts
|

Visual physiology underlying orientation and diel behavior in the sand beach amphipod Talorchestia longicornis

Abstract: SUMMARYTalitrid amphipods employ vision for zonal recovery behaviors on sand beaches and for entraining circadian activity rhythms. Using a hierarchy of methods, we examined visual spectral and response-intensity functions in Talorchestia longicornis, a species in which orientation and rhythm entrainment are wavelength-specific behaviors. Microspectrophotometry, electroretinogram recording and behavioral assays were used to determine visual pigments, retinal spectral sensitivity and wholeanimal spectral respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 44 publications
2
17
4
Order By: Relevance
“…As expected (Cohen et al 2010), both the waveforms of corneal negative- and positive responses were observed, however our data obtained from a proximal area were not stable showing both negative- and positive-responses. Therefore, we only used the corneal positive waveform obtained the electrode placed on the surface layer of crystalline cone (just below the cornea).…”
Section: Discussionsupporting
confidence: 81%
“…As expected (Cohen et al 2010), both the waveforms of corneal negative- and positive responses were observed, however our data obtained from a proximal area were not stable showing both negative- and positive-responses. Therefore, we only used the corneal positive waveform obtained the electrode placed on the surface layer of crystalline cone (just below the cornea).…”
Section: Discussionsupporting
confidence: 81%
“…In the fiddler crabs Uca thayeri and Uca pugilator, values of logk are 13.9 and 14.8, thus only slightly higher than the values we observed here (reported in Cohen and Frank, 2006). The beach-dwelling amphipod Talorchestia longicornis shows only slightly lower values of logk (dark-adapted 11.89 log photons cm −2 s −1 /light-adapted 11.97 log photons cm −2 s −1 ) than cleaner shrimp, as well as slightly longer response latencies (darkadapted 30.3 ms /light-adapted 27.7 ms) (Cohen et al, 2010). Thus, measures of sensitivity and response latency in our three species of cleaner shrimp were consistent with those of other studied crustaceans that live in a high-light environment.…”
Section: Discussion Cleaner Shrimp Visual Capabilitiescontrasting
confidence: 75%
“…Other factors are probably involved, such as the period of the day and some spectral characteristics of the two astronomical cues (e.g. Cohen et al, 2010). Finally, our results do not exclude the perception and use by sandhoppers of other celestial factors, e.g.…”
Section: The Journal Of Experimental Biology 215 (16)contrasting
confidence: 64%